The Role of the Supervisor Board in Improving Drinking Water Service for the Community of Tangerang Regency - Era Era Hia (Institut Pemerintahan Dalam Negeri (IPDN), 2019)
The study, entitled the role of the Board of Trustees in improving drinking waterServices to the public in Tangerang Regency of Banten Province. Motode research isqualitative research methods, with the determination of purposive sampling techniquethrough informants and accidental sampling. The results of this study concluded thatthe performance PDAM Tirta Kerta Raharja in serving drinking water on thecommunity in not optimal. Hence the importance of the role of the Board of Trusteesin conducting surveillance, control and management of the management and coachingagainst the PDAM in order to improve drinking water in communities in. As for therole undertaken by the Board of Trustees PDAM Tirta Kerta Raharja in improvingdrinking water services to the public are: first, the role of oversight namely conductingsurveillance against the implementation of the work programme in the entire instanceof PDAM. Second, the role of control i.e. ensure what has been planned can beimplemented properly. Third, the role of coaching that is doing the briefing, givingencouragement and motivation to the directors and the ranks of PDAM Tirta KertaRaharja. Fourth, the role of the liaison providing explanations, considerations andsuggestions to the Governors before taking a decision with regard to the managementof waterworks undertaken by the Board of Directors. Fifth, the role of the evaluatorthat is assessing the performance of Directors and reports made the Board ofDirectors.